INHIBITORY EFFECTS OF GREEN ADDITIVES ON THE CRYSTAL GROWTH OF SPARINGLY SOLUBLE SALTS - Demadis, Konstantinos D.; Oner, Mualla (NOVA SCIENCE PUBLISHERS, INC, 2009)
In this chapter the effects of environmentally friendly additives on fort-nation and growth of sparingly soluble salts are presented in a concise way. Specifically, the influence of a biodegradable, environmentally friendly polysaccharide-based polycarboxylate, carboxymethyl inulin (CMI), on the crystal growth kinetics of calcium oxalate has been studied. The spontaneous crystallization method was used to delineate the crystallization kinetics of calcium oxalate (CaC2O4, CaOx). The results demonstrate that the retardation in crystal growth is controlled by the carboxylation degree of the CMI and its concentration. These studies also show that CMI additives direct calcium oxalate crystallization from calcium oxalate monohydrate (COM) to calcium oxalate dihydrate (COD). Colloidal silica is known to be a substantial problem in silica-laden process waters. Although silica technically is not a salt, it is often categorized with them, as it brings about the same problems as mineral scale deposits (reduced heat transfer, etc.). We also report a strategy to retard silicic acid condensation in supersaturated aqueous solutions by using non-toxic, green, zwitter-ionic phosphonomethylayed chitosan (PCH). An overview of the use of green additives in water treatment is also presented.
Keywords: green chemistry; environmentally friendly; scale inhibition; calcium oxalate; additives; water treatment; polymers; silica; CALCIUM-OXALATE CRYSTAL; COLLOIDAL SILICA; WATER-SYSTEMS; HUMAN URINE; IN-VITRO; CRYSTALLIZATION; MONOHYDRATE; ACID; MACROMOLECULES; DISSOLUTION; Chemistry